Nutritional Support in Children after Cardiosurgical Operations - Z. Z. Nadiradze; Yu. A. Bakhareva; O. V. Nadiradze; L. V. Neznakhina (Общая реаниматология)
Objective: to comparatively analyze nutritional support with breast milk, standard adapted and semielementary formulas. Subjects and methods. Three groups of patients aged 3 months to 1 year who had undergone cardiac surgery under extracorporeal circulation were retrospectively studied. The criteria for enteral feeding efficiency were biochemical parameters on postoperative days 1, 2, and 5, weight accretion rates by day 10, rates of flatulence, tubal expulsion or regurgitation, and stools. Results. In Group 2, unlike Group 3, there was no adequate correction of metabolic disturbances by day 5, not only a reduction in the level of total protein and albumin, but also later recovery of hemoglobin and urea levels. Conclusion. Breast milk is not the infant food of choice in the early postoperative period.